MUKJIZAT AL-QUR’AN DALAM MEMPENGARUHI JIWA MANUSIA (Studi Komparatif Penafsiran Ibn Jarir al-Tabari dan Sayyid Qutub) - Ghozi Mubarok; Mukarromah, Wildanil (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2026)
One of the miracles of the Koran is that it can influence the human soul. Several studies have tried to formulate the term "al-I‘jaz al-Ta'thiri" as a concept to describe the influence of the Qur'an on humans. The purpose of this research is to determine the views of Ibn Jarir al-Tabari and Sayyid Qutb regarding the miracles of the Al-Qur'an in influencing the human soul. The approach used in this research is a qualitative approach in the nature of library research with documentation methods. The study results show that Ibn Jarīr al-Ṭabarī and Sayyid Quṭb agree that the Qur’an has a profound influence on the human soul, such as eliciting tears, fear of Allah, and inner tranquility, especially in the context of specific verses like QS. Al-Māidah/5:83, Yunus/10:57, and Az-Zumar/39:22-23. However, Sayyid Quṭb tends to interpret the verses in a more analytical and psychological manner, whereas Ibn Jarīr al-Ṭabarī emphasizes a traditional approach based on narrations and historical context.